ANALISIS PEMANFAATAN AKUN INSTAGRAM @ALINIA PARK AND RESORT SEBAGAI MEDIA PROMOSI DALAM MENINGKATKAN MINAT PENGUNJUNG WISATA - Leni Rayani Gorat; Andri Maijar (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
This thesis aims to increase visitor interest in Alinia Park and Resort and assess the impact of promotions through Instagram. Instagram is widely used for various activities such as entertainment, business, and information seeking. Its global reach has prompted a shift from conventional to modern promotional methods, specifically through social media. Social media promotions influence external factors that shape consumer perceptions of a product, subsequently affecting their buying interest. One of the key advantages of Instagram is the ease with which promotions can be carried out. The research employs a descriptive qualitative method to analyze and describe the data related to the issues being studied. Data was collected through observation, interviews, and documentation. The data analysis method used includes data reduction, data presentation, and conclusion drawing. The theoretical framework for this research is the marketing mix, focusing on Instagram features. The study reveals that promoting Alinia Park and Resort through Instagram involves various features like Posts, captions, Hashtags, Tags, Likes, Followers, Mentions, Geotags, Instagram Reels, Stories, and Comments. These features support the promotional process by providing information and influencing tourists to visit. Based on observations and interviews with several tourists, Instagram is found to be more effective in increasing visitor interest, as evidenced by statements from the tourists.